2018
DOI: 10.1093/biolinnean/bly120
|View full text |Cite
|
Sign up to set email alerts
|

All the better to bite you with! Striking intrasexual differences in cheliceral size define two male morphs in an Amazonian arachnid

Abstract: When two mating tactics can be successfully used by different-sized males, disruptive selection may favour morphological divergence between males, resulting in intrasexual dimorphism. Here we characterize intrasexual dimorphism based on cheliceral size in males of the harvestman Paecilaemula lavarrei. We also describe how males of the two morphs use their chelicerae in intra-and intersexual interactions, and investigate microhabitat use to infer their mating tactics. The distribution of body and cheliceral tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Our observations on male-male interactions suggest that the robust male is more aggressive than the slender male, which never initiated an attack to the robust male, but on some occasions responded to the attacks of robust males. A similar case occurs in Paecilaemula lavarrei Goodnight & Goodnight, 1942 (Cosmetidae) which inhabits the Amazon forest (Solano-Brenes et al 2018). Laboratory observations performed in this study, although with a small sample size, found that only majors initiated a contest, biting the opponent, and both minors and majors responded to the attacks with bites on the opponent's legs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our observations on male-male interactions suggest that the robust male is more aggressive than the slender male, which never initiated an attack to the robust male, but on some occasions responded to the attacks of robust males. A similar case occurs in Paecilaemula lavarrei Goodnight & Goodnight, 1942 (Cosmetidae) which inhabits the Amazon forest (Solano-Brenes et al 2018). Laboratory observations performed in this study, although with a small sample size, found that only majors initiated a contest, biting the opponent, and both minors and majors responded to the attacks with bites on the opponent's legs.…”
Section: Discussionsupporting
confidence: 66%
“…Currently, the dorsal scutum length, measuring rigid parts alone, is preferred over the total body length as a reference of the size (Acosta et al 2007). Some families in the order Opiliones have females that are smaller than males, and the intersexual dimorphism is evident not only in body size but also in other traits, such as leg armature, leg length, cheliceral size, and cheliceral shape (e.g., Buzatto & Machado 2008;Willemart et al 2009;Buzatto et al 2011;Zatz et al 2011;Painting et al 2015;Solano-Brenes et al 2018), as it seems to occur, in part, in J. decui. found that the evolution of intrasexual male dimorphism in gonyleptids is strongly correlated with intersexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism appears in various forms in Opiliones , including differences in body size, length and armature of chelicerae, legs and pedipalpi and glandular openings on legs, pedipalpi and chelicerae (e.g. Dasilva and Kury 2007 ; Buzatto and Machado 2008 ; Willemart et al 2009 ; Willemart et al 2010 ; Buzatto et al 2011 ; Zatz et al 2011 ; Painting et al 2015 ; Solano-Brenes et al 2018 ). The typical sexual dimorphism of assamiids is reinforced in the appendages of male, for example, enlarged leg II and leg IV, swollen cheliceral hand ( Sharma et al 2011 ; Kury et al 2022a ) and filiform pedipalpi in Filopalpinae ( Martens 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative reproductive tactics are widespread among the Laniatores, but also occur in some species of Eupnoi ( Buzatto and Machado 2014 ). Alternative reproductive tactics are usually coupled with male polymorphism, i.e., the presence of discrete male morphs in the same population that can be recognized by differences in body size and/or size of fighting-related traits ( Buzatto and Machado 2008 ; Zatz et al 2011 ; Painting et al 2015 ; Solano-Brenes et al 2018 ; Powell et al 2020 ; Palaoro et al 2022 ). In Serracutisoma proximum (Laniatores: Gonyleptidae), for instance, there are 2 male morphs that differ in the length of the second pair of legs ( Buzatto et al 2011 ).…”
Section: Precopulatory Phasementioning
confidence: 99%